Determinacion de los costos de produccion en la pescaderia el chinito, periodo mayo 2016 - Puchaicela Saraguro, Mery Galud (2017)
This thesis was done prior to obtaining the degree in Accounting and Auditing CPA, allowing me to apply the knowledge acquired in the university classrooms, also serves as a reference to the owner to be able to have a real knowledge of the cost of the products offered to his clients. During the cost determination process, the objectives set out at the beginning of this work were achieved through the bibliographic review of texts related to the topic; The design of an initial budget, as well as the accounting documents and records necessary for the treatment of each of the elements of the cost; A method that allowed us to set the right selling price so as to obtain a reasonable profit that allows us to continue growing and thus to become a local market as one of the establishments with the highest commercial growth at the regional level. Finally, with the results obtained it can be concluded that the cost determination is a system that the companies dedicated to the production should apply correctly because it would allow them to know for sure if the production that they produced them generated an adequate profitability through the system of the Determination of the costs by orders of production recommending to the owner of the PESCADERÍA to follow it applying to get to obtain a better productive development.